THE EFFECT OF USING COMIC STRIPS AS MEDIA ON THE ABILITY OF THE SECOND YEAR STUDENTS OF SMP TRIBHAKTI PEKANBARU IN WRITING RECOUNT TEXTS - Siska Siska; Eliwarti Eliwarti; Afrianto Afrianto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research is aimed at finding out whether or not there is a significant effect of using comic strips as media in teaching writing of the second year students of SMP Tribhakti Pekanbaru in the Academic Year 2018/2019 in writing recount text. The research design is pre-experimental research with one group pre-test – treatment – post-test design. The sample of the research was 30 students VIII 1 chosen by using cluster random sampling technique. The data were collected by giving the writing test about recount text (pre-test and post-test) to the students. The data were analyzed by using t-test formula. The results of data analysis showed that the mean score of posttest was higher than the mean score of pretest (60.05 > 53.72). The value of t-test was 12.441 while the value of t-table in significance level 5% df = 29 was 2.045. Since the value of the t-test was higher than t-table, it can be concluded that Alternative hypothesis (Ha) was accepted and Null Hypothesis (Ho) was rejected. It means that there was a significant effect of using comic strips as media on the ability in writing recount texts of the second year students at SMP Tribhakti Pekanbaru. It suggested that comic strips worked to improve students’ writing ability, especially in writing recount texts as media.Key Words: Comic Strips, Writing ability, Recount Text